Detecting the Possibility of Soil Pollution with Radon Emissions for an Area Located within Baghdad University Campus- AL-Jadiriyah - Al-Khafaji, Wadhah Mahmood Shakir; Mehdi, Ruwaida Tariq; Rejah, Basim Khalaf (Iraqi Journal of Science, 2019)
This research deals with the detection of possible surface soil pollution by radon emissions for an area located inside the university of Baghdad campus at AL-Jadiriyah / Baghdad. The area is about 5625 m2 and located near the College of Science for Women. The area used as construction rubbles dump yard in the past, while recently it is covered with Silty - Clayey soil furnished with grass and used as a playground. A surface survey performed on October 2018 by gridding the area into 36 stations where surface radiometric pollution readings recorded and soil samples collected by using an auger for the top 30 Cm which represents the root zone of the area. Soil samples tested in the laboratory by using can technique with CR-39 type track detectors, while surface readings performed by using a portable Geiger counter device. Soil surface readings and laboratory analysis results were processed by computer in order to draw contour maps which showed the variation of radon emission anomalies across the area. The aim behind this processing and interpretation is to provide an evaluation for the health environmental impact related to the radioactivity of the top soil and the area surface. The results of this study showed that radon emissions were below the standard limits and this makes it possible to invest the area for future human housing and other activities.